Study of maternal and perinatal outcome in post-dated pregnancy - Patel, Tejal L.; Rathod, Dhrutiben Amarsinhbhai (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: It has been reported that in a pregnancy which has crossed the expected date of delivery, there is an increased risk of oligohydramnios, meconium stained amniotic fluid, macrosomia, fetal postmaturity syndrome, and cesarean delivery, all of which endanger the baby as well as the mother. The present study focus to investigate maternal and perinatal outcome in postdated pregnancies. Methods: The prospective observational study included primigravida and multigravida beyond 40 weeks of gestation admitted from September 2019 to September 2020 in obstetrics and gynaecology department B. J. medical college, civil hospital, Ahmedabad. Results: Out of 100 patients, majority were primigravida 62%, meconium stained liquor with fetal distress was the most common indication for LSCS 23.5 %, fetal distress was the most common fetal complications, rate of NICU admission was 33.33% between 41 weeks 1 day to 42 weeks, rate of induced labour was 71.43% between 41 weeks 1 day to 42 weeks. 88% patients were between 40 weeks 1 day to 41 weeks. Conclusions: Prolonged pregnancy was associated with remarkable risk of perinatal complications like fetal distress, meconium aspiration syndrome, IUGR, obstetric complications like oligohydramnios, perineal tear, atonic PPH and shoulder dystocia. The adverse outcome can be reduced by making accurate gestational age and diagnosis of postterm gestation as well as identifiable and management of risk factors. Considering the maternal and neonatal morbidity associated with prolonged pregnancy, pregnancy should not be permitted to go postterm.